Geniposide ameliorates cholesterol accumulation and promotes osteoblast differentiation by mediating the GLP-1R/AMPK/SREBP2 pathway - Wang Zhan; Longhuo Wu; Shan Li; Guoqiang Yin; Jianguo Zhou; Zhenyu Wu (Journal of Orthopaedic Surgery and Research)
Abstract Background Glucocorticoid (GC)-induced OP (GIOP) is a systemic metabolic bone disease with a high risk of fracture. Recently, lipid metabolic disorders, particularly hypercholesterolemia, have been correlated to the development of OP. However, the roles of cholesterol accumulation in osteoblasts during GIOP pathological development are still unclear. Our previous study shows that intracellular cholesterol accumulation can suppress osteoblast differentiation and promote cell apoptosis. Geniposide (GEN), a natural activator of glucagon-like peptide-1 receptor (GLP-1R), exhibited protective activity against dexamethasone (DEX)-induced cholesterol accumulation and osteoblast differentiation inhibition. Sterol regulatory element-binding protein 2 (SREBP2) regulates cholesterol synthesis. Whether SREBP2 was involved in DEX-induced cholesterol accumulation and osteoblast differentiation was still unknown. Methods DEX-induced rat OP models were duplicated. Micro-computed tomography (µCT) was used to scan the proximal femurs, and hematoxylin and eosin (H&E) staining was used for histological examination. MC3T3-E1 cells were used for the cell study, and ALP and Alizarin Red S were employed to study osteoblast differentiation. pcDNA3.1-SREBP2 was used to transfect MC3T3-E1 cells. Western blotting assays were employed to study the protein expression. Results DEX enhanced the expression of SREBP2 and mTOR and promoted cholesterol accumulation and osteoblast differentiation inhibition in MC3T3-E1 cells. These could be rescued by GEN treatment. However, overexpression of SREBP2, mTOR activation, and AMPK and GLP-1R inhibition could block the protective effects of GEN. Conclusion GEN improved DEX-induced cholesterol accumulation and osteoblast differentiation inhibition by mediating the GLP-1R/AMPK/mTOR/SREBP2 signaling.